Legal Protection for Consumers as Users of Illegal Cosmetics who are not Registered by BPOM Based on Law no. 8 of 1999 concerning Consumer Protection - Shelly Adisti Setiawati; Maria Adelweys Niken Aprilia Sinaga; Sheilla Virginia Andreyn (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Human needs in modern times are very diverse. Existing human needs, not just the need for food, clothing, and boards. Currently, human needs are more than that, because in fact the fast-moving era will bring many changes in human needs, one of which is the use of cosmetics. In modern times, cosmetics are needed to support everyone's appearance, especially for women. Current technological developments are a factor influencing the emergence of various cosmetic products. This study aims to obtain accurate data and truth by following the applicable rules for legal certainty as stipulated in the provisions of Law No. 8 of 1999 concerning Consumer Protection This study uses a normative legal research method that focuses on the Law. The legal materials used in this journal are primary legal materials and secondary legal materials. The research uses a statutory approach, where researchers will examine laws related to legal issues raised in this study, and later it will be necessary to carry out further studies. This research is expected to have a positive influence on business actors and consumers to minimize arbitrary actions from business actors to guarantee the achievement of guaranteed protection for consumers in Indonesia. This research illustrates that the public as consumers of a cosmetic product, must be wise and careful in buying a cosmetic product, and there is a need for increased regulations on consumer protection and also on the application of sanctions from business actors who are not responsible in carrying out their business activities